Method for Isolation of Deoxyribonucleic Acid from Mycobacteria - Mizuguchi, Yasuo (1970)
A relatively gentle and efficient procedure for obtaining deoxyribonucleic acid from mycobacteria by the use of glycine and lysozyme is described.